Protective Effect of White-fleshed Peach ( Prunus persica (L.) Batsch) on Chronic Nicotine-induced Toxicity - Kim, Hyun-Jeong; Park, Kwang-Kyun; Chung, Won-Yoon; Lee, Sun Kyoung; Kim, Ki-Rim (Journal of cancer prevention, 2017)
Nicotine is a major toxic component of tobacco smoke and has been recognized as a risk factor to induce oxidative tissue damage, which is a precursor to cardiovascular diseases, lung-related diseases, and cancers. Peaches ( ) have been used for the treatment of degenerative disorders, such as hypermenorrhea, dysmenorrhea, and infertility in Asian countries. In this study, we investigated the effects of white-fleshed peach on the excretion of nicotine metabolites and 1-hydroxypyrene in smokers and chronic nicotine-induced tissue damages in mice. The concentrations of cotinine and 1-hydroxypyrene were measured in urine of smokers before or after intake of white-fleshed peaches. In addition, ICR mice were injected with nicotine (5 mg/kg body weight) and then orally administered with white-fleshed peach extracts (WFPE) (250 or 500 mg/kg body weight) for 36 days. The oxidative stress parameters and the activities of antioxidant enzymes were measured in liver and kidney tissues. Also, histological changes and nitrotyrosine expression were assessed. Intake of white-fleshed peaches increased the urinary concentration of nicotine metabolites and 1-hydroxypyrene in 91.67% and 83.33% of smokers, respectively. WFPE decreased the malondialdehyde levels and recovered the activities of antioxidant enzymes in nicotine-injected mice. In addition, WFPE inhibited nitrotyrosine expression and inflammatory responses in the liver, kidney, and lung tissues of nicotine-treated mice. White-fleshed peaches may increase the metabolism of toxic components in tobacco smoke in smokers and protect normal tissues against nicotine toxicity in mice. Therefore, supplementation of white-fleshed peaches might be beneficial to smokers.